2014
DOI: 10.1007/s12253-014-9757-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of YAP1 is Correlated with Progression, Metastasis and Poor Prognosis in Patients with Gastric Carcinoma

Abstract: YAP1 is overexpressed in numerous cancers, but its molecular mechanism in the carcinogenesis and clinic significance in tumor diagnosis and prognosis remains to be determined. We attempted to analyze the clinicopathologic significance of YAP1 expression and the correlation of the YAP1 levels with the progression, metastasis and prognosis of patients with gastric carcinoma. By immunohistochemistry, we determined YAP1 expression in 214 of primary gastric carcinoma (GC), 167 of matched normal gastric mucosa, 40 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 21 publications
6
51
0
Order By: Relevance
“…For example, levels of YAP mRNA in pancreatic cancer tissues were 2.5-and 1.3-fold higher than those observed in normal pancreas tissues and chronic pancreatitis tissues, respectively. Similar results have been observed in gastric and liver cancer (17,18). However, the role of YAP in the occurrence of tumors as an oncogene has been questioned (19)(20)(21).…”
Section: Discussionsupporting
confidence: 76%
“…For example, levels of YAP mRNA in pancreatic cancer tissues were 2.5-and 1.3-fold higher than those observed in normal pancreas tissues and chronic pancreatitis tissues, respectively. Similar results have been observed in gastric and liver cancer (17,18). However, the role of YAP in the occurrence of tumors as an oncogene has been questioned (19)(20)(21).…”
Section: Discussionsupporting
confidence: 76%
“…YAP and TAZ are reportedly increased in a subset of human gastric cancers, most of which are associated with poor clinical outcomes (12)(13)(14). Until now, this association has been shown only via immunohistochemistry (12)(13)(14).…”
Section: Yap Signatures Are Enriched In a Subpopulation Of Human Gastmentioning
confidence: 99%
“…Several studies have suggested a potential link between YAP/TAZ signaling and gastric cancer (12)(13)(14)(15). YAP expression is upregulated in gastric tumor samples compared to normal tissue, and the total amount of YAP expression as well as its nuclear localization are significantly correlated with poorer clinical outcomes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of PKCα protein in the pituitary tumor tissue was detected by the universal PV-9000 two-step method (24,25). Briefly, formalin-fixed paraffin-embedded tissues from 53 pituitary tumors and 5 normal pituitary tissues were cut into 4-”m slices.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%